Historical Portrait of the Progress of Ichthyology / Tableau historique des progrès de l'ichtyologie From Its Origins to Our Own Time / Depuis son origine jusqu'à nos jours - Cuvier, Georges (Archives, 2020)
A founder of comparative anatomy and a giant of nineteenth-century biology, Georges Cuvier, and his student and colleague Achille Valenciennes, brought together all that was known about fishes in their massive 22-volume Histoire naturelle des poissons published from 1828 to 1849. Despite the passage of time, this work represents a landmark in the history of science, indispensable to systematic ichthyology and to comparative biology in general. As an introduction to this monumental work, the first volume traces the development of the study of fishes as then understood-from the earliest beginnings to the first third of the nineteenth-century-and summarizes the criteria for classification that their own work would follow. This critically important essay-one of the first attempts at a comprehensive history of any major group of organisms-now appears in English alongside the original French text, beautifully illustrated and accompanied by rich annotations and commentary, serving to bring this important text to our attention and highlighting its historical significance.